A nomogram predicting severe adverse events after ureteroscopic lithotripsy: 12 372 patients in a Japanese national series. (18th December 2012) - Sugihara, Toru; Yasunaga, Hideo; Horiguchi, Hiromasa; Nishimatsu, Hiroaki; Kume, Haruki; Ohe, Kazuhiko; Matsuda, Shinya; Fushimi, Kiyohide; Homma, Yukio
<x xml:space="preserve">Abstract</x> What's known on the subject? and What does the study add? Ureteroscopic lithotripsy sometimes causes severe complications, e.g. septic shock, and the relationship between long operative duration and complication rate has been empirically recognised. But due to the rarity, evidence is limited. We analysed 12372 cases and showed that the complication rate increased according to operative duration, especially for operations taking >90 min. Also, we found that high‐volume centres had lower complication rates. Objective To develop a nomogram to predict severe adverse events (AEs) after ureteroscopic lithotripsy (URSL) including the effects of operative duration and hospital volume. Patients and Methods We identified patients undergoing URSL from the Japanese Diagnosis Procedure Combination database between 2007 and 2010, and defined severe adverse events as (i) in‐hospital mortality; (ii) postoperative medication including catecholamine, γ globulin, protease inhibitors, medications for disseminated intravascular coagulation and transfusion; and (iii) postoperative interventions including percutaneous nephrostomy, central vein catheterisation, intensive care unit, dialysis, mechanical cardiopulmonary support. Univariate and multivariate logistic regression models addressed the occurrence of severe AEs. Results Of 12 372 patients, 296 patients (2.39%) had severe AEs. Multivariate analysis showed a positive linear trend of operative duration and severe AEs (odds ratio [OR] 1.58 in 90–119 min to OR 4.28 in ≥210 min compared with ≤ 59 min; each P < 0.05) and an inverse relationship between hospital volume and severe AEs (OR 0.64 in ≥39 URSLs/year compared with ≤ 15 URSLs/year; P = 0.004) with adjustment for other significant factors including sex, age, Charlson comorbidity index, type of anaesthesia and type of admission. A nomogram and a calibration plot based on these results were well‐fitted to predict a probability between 0.01 and 0.10 (concordance index 0.677). Conclusion Severe AEs after URSL were associated with longer operative duration and lower hospital volume, and were accurately predicted using the present nomogram.